Quantitative proteomics insights into the response mechanisms of Aeromonas hydrophila to chromium stress - Huaiyao Zhang; Chenghao Shen; Xin Zeng; Xiaowei Zhang; Binghui Zhang; Yuyue Xie; Xiangmin Lin; Lingli Lian (BioMetals, 2026)

Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Overexpression of GPX4 in diabetic rat kidney alleviates renal injury induced by ferroptosis - Keping Wu; Enyi Zhu; Jiasi Chen; Qingyan Kuang; Jiawen Lin; Shuping Zhao; Xiaochang Xu; Shuping Li; Yuan Sui; Mingcheng Huang; Yimin Zhang (BioMetals, 2025)

Effects of amino acids on the germination and Cd accumulation in soybeans exposed to cadmium - Lukman Iddrisu; Jiehao Lin; Evodia Moses Mkulo; Muqadas; Zhijia Fang (BioMetals, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

The role of ferroptosis in DM-induced liver injury - Keping Wu; Jiasi Chen; Jiawen Lin; Enyi Zhu; Xiaochang Xu; Xiuhong Yan; Lang Ju; Mingcheng Huang; Yimin Zhang (BioMetals, 2024)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

Gene regulation and ionome homeostasis in rice plants in response to arsenite stress: potential connection between transcriptomics and ionomics - Guobing Lin; Li Ma; Xiaoman He; Jie Tang; Lin Wang (BioMetals, 2023)

Selenium deficiency increased duodenal permeability and decreased expression of antimicrobial peptides by activating ROS/NF-κB signal pathway in chickens - He Yujiao; Tang Xinyu; Fan Xue; Li Zhe; Peng Lin; Shi Guangliang; Li Shu (BioMetals, 2023)

Glutathione and the intracellular labile heme pool - Rosemary O’Keeffe; Gladys Oluyemisi Latunde-Dada; Yu-Lin Chen; Xiaole L. Kong; Agostino Cilibrizzi; Robert C. Hider (BioMetals, 2021)
One candidate for the cytosolic labile iron pool is iron(II)glutathione. There is also a widely held opinion that an equivalent cytosolic labile heme pool exists and that this pool is important for the intracellular transfer of heme. Here we describe a study designed to characterise conjugates that form between heme and glutathione. In contrast to hydrated iron(II), heme reacts with glutathione, under aerobic conditions, to form the stable hematin–glutathione complex, which contains iron(III). Thus, glutathione is clearly not the cytosolic ligand for heme, indeed we demonstrate that the rate of heme degradation is enhanced in the presence of glutathione. We suggest that the concentration of heme in the cytosol is extremely low and that intracellular heme transfer occurs via intracellular membrane structures. Should any heme inadvertently escape into the cytosol, it would be rapidly conjugated to glutathione thereby protecting the cell from the toxic effects of heme.

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

A direct comparison of divalent metal-ion transporter (DMT1) and hinokitiol, a potential small molecule replacement - Michael D. Garrick; Laura M. Garrick; Lin Zhao; James F. Collins; Joleen Soukup; Andrew J. Ghio (BioMetals, 2019)

Synthetic sideromycins (skepticism and optimism): selective generation of either broad or narrow spectrum Gram-negative antibiotics - Yun-Ming Lin; Manuka Ghosh; Patricia A. Miller; Ute Möllmann; Marvin J. Miller (BioMetals, 2019)

Iron chelation inhibits cancer cell growth and modulates global histone methylation status in colorectal cancer - Lin-Lin Cao; Hangqi Liu; Zhihong Yue; Lianhua Liu; Lin Pei; Junxu Gu; Hui Wang; Mei Jia (BioMetals, 2018)

Rhodium (II) complex with 2-benzoylpyridine, a novel potential chemotherapeutic drug, induces cell cycle arrest and apoptosis in HepG2 cells - Xuehong Wang; Yulan Li; Minglin Lin; Junfei Jin; Zhaoquan Huang (BioMetals, 2017)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Manganese elevates manganese superoxide dismutase protein level through protein kinase C and protein tyrosine kinase - Sufen Li; Lin Lu; Xiudong Liao; Tianquan Gao; Funing Wang; Liyang Zhang; Lin Xi; Songbai Liu; Xugang Luo (BioMetals, 2016)

Incorporation of zinc into the coccoliths of the microalga Emiliania huxleyi - Giulia Santomauro; Wei-Lin Sun; Franz Brümmer; Joachim Bill (BioMetals, 2016)

Impact of heavy metal stresses on the growth and auxin homeostasis of Arabidopsis seedlings - Rui Wang; Jiehua Wang; Lin Zhao; Shaohui Yang; Yingjin Song (BioMetals, 2015)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

EGCG inhibit chemical reactivity of iron through forming an Ngal–EGCG–iron complex - Guan-Hu Bao; Jie Xu; Feng-Lin Hu; Xiao-Chun Wan; Shi-Xian Deng; Jonathan Barasch (BioMetals, 2013)

In vitro-binding of the natural siderophore enantiomers pyochelin and enantiopyochelin to their AraC-type regulators PchR in Pseudomonas - Po-Chi Lin; Zeb A. Youard; Cornelia Reimmann (BioMetals, 2013)

Kinetics of manganese transport and gene expressions of manganese transport carriers in Caco-2 cell monolayers - Xiaoli Li; Jingjing Xie; Lin Lu; Liyang Zhang; Lingyan Zhang; Yaxue Zou; Qiuyue Wang; Xugang Luo; Sufen Li (BioMetals, 2013)

Chromium levels in insulin-sensitive tissues and the thigh bone are modulated by prednisolone and high-fat diets in mice - Po-Wen Chen; Chang Lin; Chung-De Chen; Wen-Ying Chen; Frank Chiahung Mao (BioMetals, 2013)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Isoform specific regulation of divalent metal (ion) transporter (DMT1) by proteasomal degradation - Michael D. Garrick; Lin Zhao; Jerome A. Roth; Houbo Jiang; Jian Feng; Natalie J. Foot; Hazel Dalton; Sharad Kumar; Laura M. Garrick (BioMetals, 2012)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Characterization and expression of chicken selenoprotein W - Bor-Rung Ou; Mei-Jung Jiang; Chao-Hsiang Lin; Yu-Chuan Liang; Kuei-Jen Lee; Jan-Ying Yeh (BioMetals, 2011)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Release of intracellular Zn2+ in cultured neurons after brief exposure to low concentrations of exogenous nitric oxide - Wei Lin; Bhavana Mohandas; Charles P. Fontaine; Robert A. Colvin (BioMetals, 2007)

Testing for the presence of magnetite in the upper-beak skin of homing pigeons - Lanxiang Tian; Bo Xiao; Wei Lin; Shuyi Zhang; Rixiang Zhu; Yongxin Pan (BioMetals, 2007)

Statement concerning the situation in the Wenzhou area - Baochu Lin (BioMetals, 2004)

Novel Cu(II)-quinoline carboxamide complexes: Structural characterization, cytotoxicity and reactivity towards 5′-GMP - Junyong Zhang; Xiaokang Ke; Chao Tu; Jun Lin; Jian Ding; Liping Lin; Hoong-Kun Fun; Xiaozeng You; Zijian Guo (BioMetals, 2003)

The remarkable hydrophobic effect of a fatty acid side chain on the microbial growth promoting activity of a synthetic siderophore - Yun-Ming Lin; Marvin J. Miller; Ute Möllmann (BioMetals, 2001)

Cadmium induced lipid peroxidation in rat testes and protection by selenium - Shuenn-Jiun Yiin; Chi-Liang Chern; Jenn-Yuan Sheu; Te-Hsien Lin (BioMetals, 1999)